Challenges and solutions in managing acquired joint contracture (AJC) in older adults: Insights from healthcare professionals - Anne Laure Roy; Patrice Piette; Marie Dandois; Bastien Fraudet; Emilie Leblong; Anne Le Gagne; Philippe Gallien (Archives of Gerontology and Geriatrics Plus)
Background: Acquired Joint Contracture (AJC) is a complex neuromuscular disorder marked by muscle stiffness and contractions, impacting patients' quality of life. It presents a spectrum of clinical manifestations and challenges in diagnosis and treatment. While genetic and neurophysiological factors are suspected, further research is needed to develop targeted therapies and enhance patient care, particularly in cases leading to wheelchair dependency. Design: This study comprises two phases: exploratory interviews with 12 healthcare professionals and a quantitative assessment involving 187 participants. Method: In Phase 1, expert healthcare professionals were interviewed to gather their extensive knowledge and insights on acquired deforming hypertonia and wheelchair positioning challenges. Phase 2 involved developing a structured questionnaire based on the Phase 1 findings, which comprehensively assessed the frequency, difficulty, impact, solutions, and satisfaction levels related to hypertonia and wheelchair positioning among healthcare professionals, enabling a quantitative analysis of responses. Result: Results highlight challenges associated with various forms of hypertonia, including anterocollis and hip flexion, impacting both patients and caregivers. Despite healthcare professionals' expertise, certain scenarios remain consistently challenging, emphasizing the need for enhanced awareness and education. Further research is warranted to address gaps in understanding and improve care strategies for AJC patients. Conclusion: The study underscores the complexities healthcare professionals face in managing AJC and emphasizes the imperative for continued research to enhance diagnostic and therapeutic approaches.